The complete Beethoven sonatas - Beethoven, Ludwig van 1770-1827 (Metropolitan München, 1984)
Composed for the countess Thérèse von Brunsvik, the 24th sonata is the shortest and one of the brightest sonatas ever written by Beethoven. 1983. Daniel Barenboïm is in his forties, and is already known around the globe for being an exceptional pianist. He made his debuts on stage when he was only 7. In his youth, he meets Artur Rubinstein, Zubin Mehta and Wilhelm Furtwängler ... His professors are named Nadia Boulanger, Edwin Fischer and Igor Markevitch. Often associated to Beethoven, Barenboim released in his life the Major part of the German composer's works (notably the complete piano concertos with Otto Klemperer in the 90s). In the 1980s, he records the complete piano sonatas, which are played again in a world tour in the 2000s. The recordings of the 32 piano sonatas shown here date back to the years 1983-1984, when the pianist enjoys a great reputation as a pianist. Since then, his renditions of the Beethoven piano sonatas have been considered a major reference